Microwave ablation for high-risk pulmonary nodules in patients infected with the Omicron variant of Sars-Cov-2 within 3 months: a retrospective analysis of safety and efficacy - Chen, Yuxian; Li, Yang; Meng, Hong; Li, Chunhai; Kong, Fanlei (Frontiers in oncology, 2024)
To evaluate the safety and efficacy of microwave ablation (MWA) for high-risk pulmonary nodules in patients infected with the Omicron variant within 3 months, a retrospective study was conducted. The study included patients with multiple high-risk nodules who underwent CT-guided MWA from April 2022 to April 2023. Patients were divided into an observation group and a control group. The primary endpoints were postoperative complications and hospital length of stay, while the secondary endpoint was progression-free survival (PFS). A total of 157 patients were included in the analysis, with 64 in the observation group and 93 in the control group. No deaths occurred within 30 days after MWA. In the observation group, the median follow-up time was 7 months, during which 5 patients experienced disease progression after MWA, including 3 cases of pulmonary metastases. Complications were primarily pneumothorax, pleural effusion, and hemorrhage, with an incidence rate of 57.8%, which was statistically significant (p=0.005). The median length of hospital stay was 5 days for the observation group and 6 days for the control group. There was no statistically significant difference in PFS between the two groups after the removal of lung metastases (p=0.265). CT-guided MWA is an alternative treatment for patients with high-risk lung nodules who have been infected with Omicron within the past 3 months.